Identifying lifestyle factors associated to co-morbidity of obesity and psychiatric disorders, a pilot study - Gaskell, Christine; Sarada, Padmakumari; Aleem, Eiman; Bendriss, Ghizlane (Frontiers in Public Health, 2023)
Obesity and psychiatric disorders are linked through a bidirectional association. Obesity rates have tripled globally in the past decades, and it is predicted that by 2025, one billion people will be affected by obesity, often with a co-morbidity such as depression. While this co-morbidity seems to be a global health issue, lifestyle factors associated to it differ between countries and are often attributed to more than one factor. Prior obesity studies were performed in Western populations; this is the first study that investigates lifestyle factors relating to obesity and mental health of the diverse population in Qatar, a country that has witnessed tremendous lifestyle change in a short time. In this pilot study, we surveyed 379 respondents to assess and compare the lifestyles of Qatar residents to the global population. However due to the high proportion of responses from the United Kingdom (U.K.) residents, we have made comparisons between Qatar residents and U.K residents. We used chi-square analysis, spearman rank correlation and logistic regression to compare the lifestyle factors of individuals suffering from both increased BMI and mental health conditions. The types of food consumed, stress, exercise frequency and duration, alcohol and tobacco consumption, and sleep duration, were explored and results argue that different lifestyle factors can contribute to the same health condition, suggesting different mechanisms involved. We found that both groups reported similar sleep durations (p=.800), but that perception of sleep (p=.011), consumption of alcohol (p=.001), consumption of takeaway food (p=.007), and physical activity significantly varied between the groups (p=.0001). The study examined the predictors of comorbidity in Qatar as well as U.K. populations using multivariate logistic regression analysis. The result of the study showed no statistical association between comorbidity and the predictors drinking habit, smoking, physical activity, vegetable consumption, eat outs, and sleep perception for the Qatar population, and for the combined population. This study, however showed a significant association (p=.033) between sleep perception and comorbidity for the U.K. population. We conclude that further analysis is needed to understand the relationship between specific lifestyle factors and multimorbidity in each country.